The Mediating Role of Occupational Dysfunction in the Recovery Process from Difficulty in Daily Life Among People with Severe and Persistent Mental Illness - Aki Watanabe; Takayuki Kawaguchi; Mai Sakimoto; Yuya Oikawa; Keiichiro Furuya; Taichi Matsuoka; Sosei Yamaguchi (Journal of Psychosocial Rehabilitation and Mental Health, 2026)
Abstract Psychosocial rehabilitation strategies should be expanded to address difficulties as a component of the recovery process for people with mental illness. However, empirical evidence remains limited because few longitudinal studies have examined occupational dysfunction, defined as negative experiences in daily activities, as a factor associated with recovery. This study aimed to examine the influence of difficulty in daily life and occupational dysfunction on changes in the recovery process in individuals with severe and persistent mental illness. Participants were community-dwelling individuals with severe and persistent mental illness (schizophrenia, bipolar disorder, and major depression) voluntarily responding to recruitment in 16 community facilities. Data from a longitudinal observational study with repeated assessments of the recovery process were analyzed using latent growth modeling with a Bayesian estimation approach. The hypothesized model examined the direct and indirect relationships among difficulty in daily life, occupational dysfunction, and changes in the recovery process. This multicenter study consisted of data collected from 63 participants. The results from the Bayesian latent growth modeling demonstrated good model fit (convergence statistics for Bayesian estimation: 1.001; posterior predictive p-value: 0.35) and statistical significance of the influence of difficulty in daily life and occupational dysfunction on changes in the recovery process. The findings suggested the importance of addressing occupational dysfunction as well as difficulty in daily life. Comprehensive assessment of negative experiences in daily activities may contribute to person-centered practices for the recovery process of individuals with severe and persistent mental illness.